The motivation against change in male methamphetamine users in the compulsory detoxification setting - Shen, Wenwen; Li, Longhui; Liu, Yue; Xie, Xiaohu; Chen, Weisheng; Liu, Huifen; Zhang, Wenwu; Liu, Yu; Yu, Haihang; Zhou, Wenhua (Frontiers in Psychiatry, 2023)
Aims The study was designed to develop a measurement for the motivation for and against change in methamphetamine users in the compulsory detoxification setting. Design This is a cross-sectional study. Setting The study was carried out in a compulsory detoxification center for male drug users in China. Participants A total of 228 male methamphetamine users who had undergone the program for at least 30 days. Measurements The motivation for/against change relating to compulsory detoxification was carried out using the Likert scale. A series of questionnaires were filled out by the participants, including the Egna Minnen Beträffande Uppfostran for rearing style, the Barratt Impulsiveness Scale-11, the adult ADHD self-report scale, and the Pittsburgh sleep quality index. Participants were also asked to recall the withdrawal symptoms before the program and to rate their current craving levels. Findings Motivations were grouped into three factors, namely, the expectation to use drugs upon the completion of the program (factor 1), the disagreement with the compulsory setting (factor 2), and the motivation to quit drug use (factor 3). Cronbach's alpha values were 0.8037, 0.8049, and 0.6292, respectively. The structural equation model showed that the overall motivation was characterized by motivation against change rather than that for change. The overall motivation was also directly affected by the current craving level and indirectly affected by the severity of addiction, paternal authoritarian upbringing style, and ADHD traits. Conclusion This study provided a measurement of motivation for and against change in subjects with drug misconduct and suggested that the motivation against change may disclose more psychological barriers than the motivation for change.